First, let's factor the given polynomial by grouping:
![\begin{gathered} g(x)=x^3-2x^2-2x+4\\ \\ g(x)=x^2(x-2)-2(x-2)\\ \\ g(x)=(x^2-2)(x-2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dfzpdpq7w07vbxo7yp5az648zcu3lw0jb5.png)
From the factor (x - 2), we can identify that x = 2 is one zero of the polynomial function.
Then, to find the other two zeros, let's equate the first factor to zero:
![\begin{gathered} x^2-2=0\\ \\ x^2=2\\ \\ x=\pm√(2)\\ \\ x_1=√(2)\\ \\ x_2=-√(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q5p035t8hxxin9828cj3ticieexdif94k4.png)
Therefore the zeros of this function are 2, √2 and -√2.